PSYCHOLOGIZATION OF NEW SOCIAL MOVEMENTS: THE RHETORIC OF IDENTITY AS A SYMPTOM OF FAMILIAL POWER - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Umanistice)
Representatives of contemporary social movements – feminism, the LGBT movement, and eco-activism – increasingly employ the term “identity” in their rhetoric. The paper explores the causes and consequences of modern social movements using the psychological concept in formulating their demands. The methodological foundation of the study is based on Jan De Vos’s theory of psychologization and Michel Foucault’s concept of psychiatric power. Through this analytical lens, the following conclusions are drawn: first, new social movements are subject to psychologization and operate within the logic of psychological thinking, that is, by the notions of truth and reality inherent in psychology as a cultural phenomenon; second, despite their opposition to power and culture, they employ similar governance mechanisms; third, adherence to psychological thinking leads to ideological paradoxes within contemporary social movements. Keywords: identity, new social movements, feminism, LGBT, ecological movement, psychologization, psychiatric power.